Implications of Project Delaying in Community Building Construction Towards Client Satisfaction - Megat Muhammad Azhan, Puteri Anis Farhana; Nor Fadhilah Mohd Salleh,; Mohamad, Mimi Mohaffyza (Online Journal for TVET Practitioners, 2023)
One of the main criteria for project success is the timely completion of building projects. In the end, a project's inability to be finished on time will cause a delay. The construction of community buildings in Felda was not an exception to the global phenomenon of construction delays. The main goals of this study were to pinpoint the implications of project delays as well as practical remedies to the issues. Several interview sessions were conducted to collect information from various viewpoints, experiences, and positions towards eight (8) participants. In this study, quantitative approach was used which was the thematic analysis method was used to analyse the data and identify themes for the implications of delays and effective solutions. This study identified several main themes, namely cost, quality, time, and client satisfaction. An effective solution was also found through the comparison of the participants' answers from the interview sessions. Project knowledge, management knowledge, and regular progress meetings were among the important techniques identified through the survey. The study conducted had been well implemented and had achieved the study’s objectives which are implications and effective solutions for project delaying. The relevance of studying these issues were to gain a better grasp of the ramifications of the implications that will be accepted in terms of client satisfaction. The results of this study should help those involved in the construction of Felda community buildings in terms of making decisions and making appropriate preparations if a similar situation occurs in the future. Through this, researcher had list out recommendation which would help in future studies. The recommendation was made for students or researchers which aiming to continue in implementing research regarding this study of implications and effective solutions of project delaying in Felda Community Building. The researcher should focus and concentrate more towards the region and state which have larger amount of community building projects.